(untitled) (Thobaqot: Jurnal Ilmu Hadis, 2023)
This study examines hadith from the view of the PERSIS Organization (Islamic Unity) with a comprehensive library research approach. This study refers to works that examine the PERSIS Organization and its thoughts on hadith, as well as the use of hadith in the PERSIS Organization. The PERSIS Organization is a community organization that was born in the early 20th century, which is also included in the Islamic reform movement organization. The focus of this study is how the PERSIS Organization understands the hadith of the prophet and applies it to exploring the law. However, this understanding needs to be analyzed more deeply, which will then be studied further from the view of the main figure in the PERSIS Organization (Ahmad Hassan) on a hadith. The methodology of this study includes collecting and analyzing relevant literature sources to explore scientific explanations of hadith from the perspective of the PERSIS Organization. This finding opens up space for further discussion regarding the contribution of the PERSIS Organization to hadith.